A remarkable new species of the magnus species-group of Cryptocellus (Arachnida, Ricinulei) from Ecuador, with observations on the taxonomy of the New World genera - Botero-Trujillo, Ricardo; Valdez-Mondragón, Alejandro (Zootaxa, 2016)
A new ricinuleid species, Cryptocellus chimaera sp. nov., is described based on a male specimen from Northwest Ecuador (Esmeraldas, Reserva Ecológica Mache-Chindul, Estación Biológica Bilsa). This species is unique among all Cryptocellus in having very large longitudinal carapacial translucent areas together with a markedly incrassate femur of leg II. Representing only the second species of the order described from Ecuador, C. chimaera sp. nov. is assigned to the magnus species-group of Cryptocellus Westwood, 1874. Cryptocellus chimaera sp. nov. is remarkable, for its morphology resembles that of Cryptocellus magnus Ewing, 1929, especially with regard to the male copulatory apparatus, although both resemble Pseudocellus Platnick, 1980, due to the presence of diffuse longitudinal carapacial translucent areas. Along with the new species description, a comparative diagnosis and supplementary images are provided for C. magnus. Based on direct observations of some species belonging to the five species-groups of Cryptocellus, we discuss on the occurrence of different morphologies of carapacial translucent areas within the genus. We deem it important to continue the survey of morphological characters, especially within Cryptocellus, in order to increase our understanding of the species-groups and to unravel their relationships.